(untitled) (Web of Teachers: Inderscience Research, 2025)
The territory of Uzbekistan provides unique opportunities for agriculture with its geographical location, climatic conditions and variety of soil types. In order to effectively take advantage of these opportunities, it is necessary to study and practice in depth the processes of welding, fertilizing and growing plants. Each of these processes requires specific technological approaches and knowledge, and must also be carried out adapted to natural conditions.